Some remarks about the conception of executive power in the 1997 Polish Constitution (Contemporary Central & East European Law, 2002)
This text is about Polish Constitution from 1997 and the division of powers (legislature, executive, judiciary). Also, Executive system have got division on President and Prime Minister. Sometimes these divisions can involve conflicts, but they are necessary. In article author also make comparisons between polish and french political system.This article i san updated verion of a text published in: Instytucje współczesnego prawa administracyjnego. Księga jubileuszowa prof. Józefa Filipka, Kraków 2001.